Heterointerface‐Modulated Synthetic Synapses Exhibiting Complex Multiscale Plasticity - Xingji Liu; Yao Ni; Zujun Wang; Sunfu Wei; Xiao′en Chen; Jingjie Lin; Lu Liu; Boyang Yu; Yue Yu; Dengyun Lei; Yayi Chen; Jianfeng Zhang; et al. (Advanced Science)
Abstract An asymmetric dual‐gate heterointerface‐regulated artificial synapse (HRAS) is developed, utilizing a main gate with distinct ion concentrations and a lateral gate to receive synaptic pulses, and through dielectric coupling and ionic effects, formed indium tin zinc oxide (ITZO) dual‐interface channels that allow precise control over channel charge, thereby simulating multi‐level coordinated actions of dual‐neurotransmitters. The lateral modulation of the lateral gate significantly regulates ionic effects, achieving the intricate interplay among lateral inhibition/enhancement and short‐/long‐term plasticity at a multi‐level scale for the first time. This interplay enables the HRAS device to simulate frequency‐dependent image filtering and spike number‐dependent dynamic visual persistence. By combining temporal synaptic inputs with lateral modulation, HRAS harnesses spatiotemporal properties for bio‐inspired cryptographic applications, offering a versatile device‐level platform for secure information processing. Furthermore, a novel dual‐gate input neural network architecture based on HRAS has been proposed, which aids in weight update and demonstrates enhanced recognition capabilities in neural network tasks, highlighting its role in bio‐inspired computing.